2011
DOI: 10.1001/jama.2011.656
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Vitamin A or Beta Carotene Supplementation on Pregnancy-Related Mortality and Infant Mortality in Rural Bangladesh

Abstract: clinicaltrials.gov Identifier: NCT00198822.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
137
0
5

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 125 publications
(148 citation statements)
references
References 26 publications
6
137
0
5
Order By: Relevance
“…Details of the trial were published elsewhere (16,17) . In brief, once enrolled in early pregnancy, a baseline interview was conducted to collect, among other information, demographic and socio-economic status as well as reproductive history.…”
Section: Methodsmentioning
confidence: 99%
“…Details of the trial were published elsewhere (16,17) . In brief, once enrolled in early pregnancy, a baseline interview was conducted to collect, among other information, demographic and socio-economic status as well as reproductive history.…”
Section: Methodsmentioning
confidence: 99%
“…Supplementation of vitamin A during pregnancy in an undernourished population in Nepal has also been associated with improved offspring lung function [33], however; it did not decrease risk of asthma [34]. Supplementation of newborns with vitamin A in Bangladesh improved infant survival [35], however other studies have shown no effect of vitamin A supplementation on infant or maternal survival [36,37]. A 2016 birth cohort study was conducted to assess the effects of vitamin supplementation during pregnancy on child behavior.…”
Section: Vitamin a Compounds And Infant Feedingmentioning
confidence: 99%
“…También se ha propuesto una posible protección de la piel frente a daños de la radiación solar 41 , una posible actividad reguladora sobre el sistema inmunológico en líneas celulares 60 , y la posible reducción de la adiposidad y tamaño de los adipocitos en ratones 61 . Además, se ha propuesto que el efecto antioxidante de los carotenoides de la dieta guarda relación con la protección de la degeneración macular tardía asociada a la edad 62 , así como un mejor desarrollo y crecimiento normal del embrión, atenuando la incidencia de parto prematuro 63 .…”
Section: Otros Carotenoidesunclassified